Risk factors associated with musculoskeletal disorders among professional drivers in Asian countries: a systematic review - Choy, Min Yap; Hanif Farhan Mohd Rasdi; Wen, Xin Lim (Penerbit Universiti Kebangsaan Malaysia, 2023)
Musculoskeletal disorders (MSDs) are injuries in the musculoskeletal system caused by sustained or sudden exposure to repetitive motion, vibration, force, and awkward positions. Professional drivers are one of the working populations with a high risk of developing MSDs. Several studies had examined the prevalence and risk factors (RFs) for MSDs among professional drivers. Thus, this systematic review aims to analyze the literature and report the risk factors associated with MSDs among professional drivers in Asian countries. Published literature was systematically searched through EBSCOhost, Web of Science, and OVID. Studies which met the inclusion criteria were methodologically appraised using the Appraisal Tool for Cross-Sectional Studies (AXIS). Based on the studies included, the RFs reported to be significantly associated with MSDs among professional drivers included physical RFs, individual RFs, and psychosocial RFs. There were some RFs that did not fall into the three categories. The most frequently and comprehensively investigated RFs were the physical RFs. In conclusion, there were various RFs associated with MSDs among professional drivers in Asian countries. Further studies should be conducted to understand MSDs among professional drivers in different contexts and circumstances. A holistic and multidisciplinary approach should be used to develop effective management and preventive techniques to address this common occupational problem affecting a large proportion of the working population.